Immunological Changes Induced in Peach Allergy Patients with Systemic Reactions by Pru p 3 Sublingual Immunotherapy. Issue 3 (8th January 2018) - Palomares, Francisca; Gomez, Francisca; Bogas, Gador; Campo, Paloma; Perkins, James Richard; Diaz‐Perales, Araceli; Rodriguez, Maria J.; Prieto, Ana; Barber, Domingo; Torres, María J.; Mayorga, Cristobalina
Abstract : Scope: Sublingual immunotherapy using peach extract enriched in Pru p 3 (Pru p 3‐enriched‐SLIT) brings a new perspective to treating patients with allergy to lipid transfer proteins. We evaluate the immunological changes induced by Pru p 3‐enriched‐SLIT during one year. Methods and results: Three groups are included: peach allergic patients who receive Pru p 3‐enriched‐SLIT, peach allergic untreated patients, and controls. Peripheral blood mononuclear cells are obtained before treatment and at different time‐points. Monocyte‐derived dendritic cells (moDCs) maturation and lymphocyte proliferation are assessed by flow cytometry. Data showed a significant reduction of moDCs maturation status during one year of treatment and an increase in PD‐L1. Moreover, we observed a significant decrease of the Pru p 3‐specific proliferation of effector cells and an increase in regulatory T (Treg) cells with higher PD‐L1 expression and IL‐10 production. These are observed in patients treated only. Conclusion: Successful Pru p 3‐enriched‐SLIT is linked to an important immunosuppression of allergen‐specific effector T cells, potentially due to an increase of allergen‐specific Treg cells. These cellular changes are orchestrated by the activity of moDCs promoting the expression of PD‐L1 that will participate in the regulatory response. These changes may serve as biomarkers during SLIT alongside other features such as IgE/IgG4 ratio. Abstract : Peach is an important cause of plant allergy in Mediterranean areas. The major peach allergen is Pru p 3, a nonspecific lipid transfer protein associated with the complex clinical entity known as LTP‐syndrome. In this work, it is shown that successful SLIT with Pru p 3 is linked to the modulation of Pru p 3‐specific effector cells, including Pru p 3‐specific Treg cells.